Oxidative Toxicology of Bleomycin: Role of the Extracellular Redox Environment - Allawzi, Ayed (Curr Opin Toxicol, 2018)
Bleomycin is a commonly used cancer therapeutic that is associated with oxidative stress leading to pulmonary toxicity. Bleomycin has been used in animal studies to model pulmonary fibrosis, acute respiratory distress syndrome, and pulmonary hypertension secondary to interstitial lung disease. The toxicity with bleomycin is initiated by direct oxidative damage, which then leads to subsequent inflammation and fibrosis mediated by generation of both extracellular ROS and intracellular ROS. While most studies focus on the intracellular ROS implicated in TGFβ signaling and fibrosis, the changes in the extracellular redox environment, particularly with the initiation of early inflammation, is also critical to the pathogenesis of bleomycin induced injury and fibrosis. In this review, we focus on the role of extracellular redox environment in bleomycin toxicity, with attention to the generation of extracellular ROS, alterations in the redox state of extracellular thiols, and the central role of the extracellular isoform of superoxide dismutase in the development of bleomycin induced injury and fibrosis.